Onsite and laboratory assessment of repair mortars for reinforced concrete floor slabs in heritage buildings - Franzoni, Elisa; Pizzigatti, Cesare (Frontiers in Materials, 2024)
The conservation and repair of XX century architectural heritage built with reinforced concrete is becoming more and more important and requires suitable materials and technical solutions. In particular, effectiveness, compatibility and durability must be ensured, in spite of the limited extent of demolition allowed by the local authorities, and the literature in this field is still limited.In this paper, an experimental campaign was carried out in an historic reinforced concrete floor slab, where different repair mortars were used. After some on-site testing on the corrosion potential, the concrete beams of the slab were integrally cut and transported to the laboratory for a series of systematic tests, aimed at investigating the performance and compatibility of the repair materials, as well as any possible issues hindering the success of this structural intervention. The filling ability, physical compatibility, chemical compatibility and mechanical compatibility of the repair mortars and the corrosion behavior of the steel reinforcement were investigated, deriving some results of general interest, which may contribute to a better insight about the repair of heritage concrete floor slabs.